Carrier density distribution in silicon nanowires investigated by scanning thermal microscopy and Kelvin probe force microscopy. (December 2015) - Wielgoszewski, Grzegorz; Pałetko, Piotr; Tomaszewski, Daniel; Zaborowski, Michał; Jóźwiak, Grzegorz; Kopiec, Daniel; Gotszalk, Teodor; Grabiec, Piotr
Highlights: We present results of scanning thermal microscopy (SThM) and Kelvin probe force microscopy (KPFM) investigations of 100-nm silicon nanowires. AFM-based experimental temperature and potential maps are compared with FEM simulations of electron concentration and potential distribution. Recorded maps and simulation results are consistent, which means that AFM-based methods can be used for surface imaging of carrier density distribution in working semiconductor devices. Pinch-off effect occurring in the investigated nanowire is shown using the SThM temperature map. Abstract: The use of scanning thermal microscopy (SThM) and Kelvin probe force microscopy (KPFM) to investigate silicon nanowires (SiNWs) is presented. SThM allows imaging of temperature distribution at the nanoscale, while KPFM images the potential distribution with AFM-related ultra-high spatial resolution. Both techniques are therefore suitable for imaging the resistance distribution. We show results of experimental examination of dual channel n -type SiNWs with channel width of 100 nm, while the channel was open and current was flowing through the SiNW. To investigate the carrier distribution in the SiNWs we performed SThM and KPFM scans. The SThM results showed non-symmetrical temperature distribution along the SiNWs with temperature maximum shifted towards the contact of higher potential. These results corresponded to those expressed by the distribution of potential gradient along the SiNWs, obtained using the KPFM method. Consequently, non-uniform distribution of resistance was shown, being a result of non-uniform carrier density distribution in the structure and showing the pinch-off effect. Last but not least, the results were also compared with results of finite-element method modeling.